A hydrogen-sensitive analysis of the structure of deuterated liquid formamide. (2nd November 2018) - Fathi, Sonia; Bahri, Mohamed; Nasr, Salah
ABSTRACT: Structural investigations of deuterated liquid formamide were performed by using neutron scattering, ab-initio calculations and classical Molecular Dynamics (MD) simulations. The recorded neutron data are analysed to yield the total structure factor SM (Q), the molecular form factor F (Q), the distinct pair correlation function gL (r) and particularly the deuterium-oxygen signature of H-bond interactions. Neutron scattering data, as well as recent x-ray studies, clearly show that the local order of the liquid is largely described by one dimer, two trimers and one tetramer. Molecular Dynamics simulations show that neutron scattering data can be reproduced by three different force fields.